The dog that didn't bite: Sudden stops in emerging and developing countries during COVID-19 - Eduardo A. Cavallo; Juan Hernández; María José González; Andrew Powell (Inter-American Development Bank (IDB), 2023)
Despite an initial reversal of capital inflows, the COVID-19 pandemic resulted in relatively mild impacts on net capital flows to Emerging and Developing Economies. In contrast to previous crises, gross capital inflows offset residents' outflows, resulting in relatively stable net capital flows and modest current account adjustments. Liquid international markets, access to official resources, and sound fundamentals allowed for capital inflows, thus preventing the additional costs of widespread Sudden Stops during the pandemic. Still, we show a relatively simple model predicted Sudden Stops in net flows reasonably well in countries with weaker fundamentals.
Keywords: F30; F32; F40; 330; Sudden stops; Capital flows; Balance of Payments; Capital Account; COVID-19; Emerging and Developing Economies